Permainan Merobek Kertas dalam Meningkatkan Kemampuan Motorik Halus AUD di TK Zia Salsabila - Annisa Vani Ramadhani,; Nur Hidayah,; Silvia Zahra,; Widia Ulan Dary DN,; Khadijah, (NANAEKE: Indonesian Journal of Early Childhood Education, 2022)
The activity of tearing paper in early childhood is important because it can entertain and create fun feelings. Muscles, nerves, the brain, and fingers are all involved in the act of tearing paper. Children are taught to tear properly and freely, and as their fingers become more flexible, basic patterns are eventually introduced, followed by object-specific patterns. If done diligently, these aspects will be harmonized. The type of research used is action research and the research sample is early childhood at IT Zia Salsabila Kindergarten. Methods of data collection using documentation and observation techniques. Data analysis used descriptive analysis. The results of the study illustrate that children's fine motor skills can be improved through tearing paper activities.